The impact of an immunization training certificate program on the perceived knowledge, skills and attitudes of pharmacy students toward pharmacy-based immunizations - Marcum ZA; Maffeo CM; Kalsekar I (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Objective: To assess the impact of a national immunization training certificate program on the perceived knowledge, skills and attitudes of pharmacy students toward pharmacy-based immunizations.Methods: The study design utilized a pre- and post-survey administered to pharmacy students before and after the American Pharmacists Association's (APhA) Pharmacy-Based Immunization Delivery program. The primary outcome explored was a change in the perceived knowledge, skills, and attitudes of the pharmacy students. A five-point Likert scale (i.e. strongly agree = 5, strongly disagree = 1) was used for measuring the main outcomes, which was summated by adding the individual item scores in each section to form a composite score for each outcome. Results: The certificate training program resulted in a significant improvement in knowledge (38.5% increase in score, p<0.001) and skills (34.5% increase in score, p<0.001), but not attitudes (1% increase in score, p=0.210).Conclusions: The national immunization training certificate program had a positive impact on the perceived knowledge and skills of pharmacy students. However, no change was observed regarding students' perceived attitudes toward pharmacy-based immunizations.